2013
DOI: 10.1155/2013/906912
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antimicrobial Activity of Chromium(III) and Ruthenium(II) Complexes onStaphylococcus aureusandEscherichia coli

Abstract: The prevalence of antibiotic resistance has resulted in the need for new approaches to be developed to combat previously easily treatable infections. The main aim of this work was to establish the potential of the synthetic α-diimine chromium(III) and ruthenium(II) complexes (where the α-diimine ligands are bpy = 2,2-bipyridine, phen = 1,10-phenanthroline, and dppz = dipyrido[3,2-a:2′,3′-c]-phenazine) like [Cr(phen)3]3+, [Cr(phen)2(dppz)]3+, [Ru(phen)3]2+, and [Ru(bpy)3]2+ as antibacterial agents by generating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…An earlier study has shown the importance of Cr doping in metal oxide nanoparticles in the antibacterial activity [39]. In the present study, though Cr-doped ZnO showed the synergetic effect on the antibacterial activity, however, the reports on chromium oxide alone showed independent antibacterial action in different bacterial strains [40,41]. It seems that the explanation of a detailed mechanism of the activities of the undoped and metal-iondoped ZnO is still under debate.…”
Section: Resultsmentioning
confidence: 57%
“…An earlier study has shown the importance of Cr doping in metal oxide nanoparticles in the antibacterial activity [39]. In the present study, though Cr-doped ZnO showed the synergetic effect on the antibacterial activity, however, the reports on chromium oxide alone showed independent antibacterial action in different bacterial strains [40,41]. It seems that the explanation of a detailed mechanism of the activities of the undoped and metal-iondoped ZnO is still under debate.…”
Section: Resultsmentioning
confidence: 57%
“…MIC A+B is the MIC of compound A in the combination with compound B and vice versa for MIC B+A , whereas MIC A or MIC B are the MIC of the compound alone. The combination effect is defined as synergy when FIC ≤ 0.5, additive when 0.5 < FIC ≤ 1.0, no interaction when 1.0 < FIC ≤ 4.0, and antagonism when FIC > 4.0 ( Páez et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Osella and co-workers [8] inserted a ferrocenyl group into the side chain of the chloroquine, and it has been reported that the resulting compound ferroquine was much safer and more effective in mice, as well as non-mutagenic. Páez and co-workers [9] synthesized complexes of α-diimine chromium (III), and the results showed that they exhibited antimicrobial activity against Gram-positive and Gram-negative bacteria. The study also showed that the chromium (III) complexes of α-diimine when combined with ciprofloxacin, an important synergistic effect was observed for the inhibition of Staphylococcus aureus and Escherichia coli.…”
Section: Synthesis Of Benzylpenicillin -Cr(iii) Complexmentioning
confidence: 99%